2019
DOI: 10.1007/s11356-019-04755-5
|View full text |Cite
|
Sign up to set email alerts
|

Natural disasters and economic losses: controlling external migration, energy and environmental resources, water demand, and financial development for global prosperity

Abstract: The objective of the study is to examine the impact of natural disasters on external migration, price level, poverty incidence, health expenditures, energy and environmental resources, water demand, financial development, and economic growth in a panel of selected Asian countries for a period of 2005-2017. The results confirm that natural disasters in the form of storm and flood largely increase migration, price level, and poverty incidence, which negatively influenced country's economic resources, including e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Specifically, during the 20th century, the global temperature increased by 0.5 °C and by the end of the current century it is expected to have increased by between 1.5 and 5.8 °C [ 1 ]. In recent decades, interest in the effects of climate change with regard to strengthening the intensity of abiotic stress has increased, in order to improve the abiotic stress tolerance of plants [ 2 ]. In this sense, previous works have reported that heat stress induces a set of physiological and biochemical reactions in cauliflower metabolism, activating various adaptive processes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, during the 20th century, the global temperature increased by 0.5 °C and by the end of the current century it is expected to have increased by between 1.5 and 5.8 °C [ 1 ]. In recent decades, interest in the effects of climate change with regard to strengthening the intensity of abiotic stress has increased, in order to improve the abiotic stress tolerance of plants [ 2 ]. In this sense, previous works have reported that heat stress induces a set of physiological and biochemical reactions in cauliflower metabolism, activating various adaptive processes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The previous literature predominantly used different innovation indicators in carbon mitigating agenda; for instance, Zhang et al [63] presented four different types of innovation in order to improve environmental performance, i.e., (i) innovation performance measured by energy efficiency, (ii) innovation resources measured by R&D expenditures, (iii) knowledge innovations measured by patent applications, and (iv) innovation environment measured by pollution governance. Ganda [64] used different innovation investments in the carbon mitigating model and argued that R&D expenditures, R&D personnel, and patent rights have a differential impact on carbon emissions across countries. Similarly, the earlier studies primarily used different innovation formulations to achieve energy efficiency and ESA, i.e., R&D expenditures, environmental technology, and green products [65], eco-innovation and green R&D practices [66], technology-based innovation [67], low-carbon innovation [68], green patents [69], triadic patent family [70], and RE technology innovation [71].…”
Section: Theoretical Considerationmentioning
confidence: 99%
“…Increasing of population growth, industrialization, shortage, and in some cases, the destruction of natural resources (1,2), have made human beings to think about and reflect on the type and manner of their interaction with the environment (3,4). In order to have a proper management system, measurement tools should be created (5).…”
Section: Introductionmentioning
confidence: 99%